2018
DOI: 10.1007/s10973-018-7067-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in athlete’s response to strength effort in normobaric hypoxia

Abstract: The hypoxia may be used during exercise training sessions in humans with the aim of improving athletic performance. The effect of normobaric hypoxia strength training on thermal properties of blood serum has been evaluated in a group of 12 male and female athletes using differential scanning calorimetry (DSC). Each athlete was tested under normoxic and simulated hypoxic (4000 m, F i O 2 = 13% and 5000 m, F i O 2 = 11.3%) conditions during squats with a barbell (70% 1RM) exercise. A substantial inter-individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It is sensitive to the up-or down-regulation of proteins and the modified thermal stability of major proteome components resulting from changes in interactions between blood plasma/serum proteins and disease-related metabolites. Earlier data from our laboratory have indicated that exercise training can also modulate the calorimetric profile of blood serum [53][54][55].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is sensitive to the up-or down-regulation of proteins and the modified thermal stability of major proteome components resulting from changes in interactions between blood plasma/serum proteins and disease-related metabolites. Earlier data from our laboratory have indicated that exercise training can also modulate the calorimetric profile of blood serum [53][54][55].…”
Section: Introductionmentioning
confidence: 92%
“…The utility of DSC method for clinical application (diagnosing, classifying and monitoring patients) and in sport medicine is extensively discussed by scientists in recent years [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. DSC has been widely applied to the analysis of blood plasma, serum or other biofluids to obtain information on the health status of the person examined.…”
Section: Introductionmentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) has found wide application in medical and biological sciences [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Attempts to use the DSC method for clinical purposes have been made for several years [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For several years, many attempts have been made to apply the differential scanning calorimetry (DSC) method in various areas of medical diagnostics and sports medicine. DSC profiles of biological fluids can be a source of valuable information about the health of patients as well as athletes [15][16][17][18][19][20][21][22][23][24][25][26][27]. The DSC method was used in patients with multiple disease entities [15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The DSC method was used in patients with multiple disease entities [15][16][17][18][19][20][21][22][23][24]. The branch of research among athletes is just developing [25][26][27]. Further research is needed on various groups of athletes to effectively support sports training and help in the case of problems related to the health of athletes.…”
Section: Introductionmentioning
confidence: 99%